The Role of the Hospital Environment in the Prevention of Healthcare-Associated Infections by Contact Transmission. (October 2013) - Steinberg, James P.; Denham, Megan E.; Zimring, Craig; Kasali, Altug; Hall, Kendall K.; Jacob, Jesse T.
OBJECTIVE: This article describes the role of the hospital environment in the spread of pathogens by direct and indirect contact. In addition, the prevention of transmission through interventions involving the built environment is discussed. BACKGROUND: The hospital environment can become contaminated with pathogenic microorganisms, some of which can persist for long periods of time. Although contamination is common, the contribution of the hospital environment to the development of healthcare-associated infections remains unclear. In part spurred by the development of newer technologies to enhance environmental cleaning or to prevent contamination, research into the role of the environment in causing healthcare-associated infections has accelerated. TOPICAL HEADINGS: A review of the recent literature finds an increasing body of evidence implicating contaminated surfaces in patient care areas in the transmission of pathogens and the development of infections. Single-patient rooms and optimally placed alcohol hand rub dispensers and other design features can mitigate infection risk. Enhanced environmental cleaning including touchless technologies and self-cleaning surfaces can reduce environmental contamination and may prevent infections. CONCLUSIONS: The hospital environment contributes to transmission of pathogens in hospitals and to the development of healthcare-associated infections. Newer technologies to prevent environmental contamination or to enhance cleaning are promising although additional studies with the endpoints of reduction of infections are needed before the role of these technologies is known.